Impact of different priming and sowing techniques in combination with different seed rates on wheat growth and yield - Samiullah Khan Ranazai; Muhammad Sadiq; Muhammad Safdar Baloch; Huma Qureshi; Tauseef Anwar; Abdullah A. Alarfaj; Mohammad Javed Ansari (Scientific Reports)
Abstract Wheat (Triticum aestivum L.) is a staple crop of immense economic importance, especially in the agronomic context of Dera Ismail Khan, Khyber Pakhtunkhwa (KPK), Pakistan. Understanding the effects of various agronomic practices, such as priming techniques, sowing methods, and seed rates, on wheat yield and growth is crucial for optimizing production and ensuring regional food security. To study the effects of priming and sowing techniques in combination with seed rates on short (Israr Shaheed) and long (Gomal) duration, three experiments were conducted at the agronomic research site of Gomal University, Dera Ismail Khan, Pakistan, wheat varieties. In the first experiment, various priming techniques were used. Among different techniques used Farmyard manure priming produced the tallest plants at 111.3 and 125.3 cm, the maximum number of tillers (335.7 and 345.0 m-2), longest spikes (8.6 and 7.6 cm), maximum spikelets (27.2 and 31.0 spike-1), maximum number of grains (45.5 and 48.7 spike-1), maximum grain yield (4.4 and 4.6 t ha-1) and maximum harvest index (38.7 and 41.5%) respectively for Israr Shaheed and Gomal. Conversely, compost manure produced heavier grains than other interactions (49.2 and 42.3 g) while sodium chloride showed the maximum biological yield (12.4 and 11.8 t ha-1) for Israr Shaheed and Gomal correspondingly. In 2nd experiment, different sowing methods were tested on two wheat varieties Israr Shaheed and Gomal. Dry sowing followed by flooding produced tallest plants measuring (105.5 and 101.7 cm), maximum number of tillers (398.2 and 406.7 m-2), longest spikes (8.3 and 7.2 cm), maximum spikelets (29.8 and 35.5 spike-1), maximum number of grains (54.3 and 51.6 spike-1) and maximum grain yield (4.3 and 4.6 t ha-1) respectively for Israr Shaheed and Gomal. Israr Shaheed and Gomal showed maximum 1000-grain weights (45.3 and 45.0 g) in sprouted seeding in flooded fields respectively. The highest biological yield (13.6 t ha-1) was in dry seed in the flooded field while the maximum harvest index (33.5 and 33.9%) was recorded in soaked seed followed by flooding for Israr Shaheed and Gomal. In the last experiment, different seed rates were studied. The results showed that plants grown with seed rate 150 kg ha-1 showed the tallest plants at 111.0 and 111.7 cm, maximum number of tillers (411.6 and 408.2 m-2), longest spikes (7.8 and 7.7 cm), maximum spikelets (34.3 and 34.3 spike-1), maximum number of grains (50.8 and 47.2 spike-1), maximum grain yield (4.6 and 4.5 t ha-1) and maximum harvest index (38.4 and 36.7%) respectively for Israr Shaheed and Gomal. The maximum number of 1000-grains weight (g) was found on 200 and 250 kg ha-1 for Israr Shaheed and Goma-8, respectively giving 45.2 g while biological yield was the highest in 175 kg ha-1 respectively. Conclusively, the results indicated that yield and yield attributes in wheat were enhanced up to 150 kg ha-1 seed rate when interacted with farmyard manure priming along with dry sowing of seed followed by flooding. Future research should explore the integration of advanced irrigation techniques and nutrient management practices to further enhance wheat productivity in the Dera Ismail Khan region.